2006
DOI: 10.1080/02699050600789447
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of dexmedetomidine in neurosurgical patients

Abstract: Dexmedetomidine can be a safe and effective sedative agent for neurosurgical patients. A loading infusion should be avoided and higher maintenance doses may be required to ensure adequate sedation. Further studies are necessary to establish an optimal dosage regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
51
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 20 publications
1
51
0
2
Order By: Relevance
“…Dexmedetomidine continues to gain popularity as a sedative agent; it is also used in patients with traumatic brain injury because of its benefi cial effects on intracranial pressure (ICP) and CBF [24][25][26][27]. Dexmedetomidine has the potential to decrease blood pressure (BP) in a dose-dependent manner due to its alpha-2 agonist activity on the sympathetic ganglia and the resulting sympatholytic effects [10,28].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine continues to gain popularity as a sedative agent; it is also used in patients with traumatic brain injury because of its benefi cial effects on intracranial pressure (ICP) and CBF [24][25][26][27]. Dexmedetomidine has the potential to decrease blood pressure (BP) in a dose-dependent manner due to its alpha-2 agonist activity on the sympathetic ganglia and the resulting sympatholytic effects [10,28].…”
Section: Discussionmentioning
confidence: 99%
“…Animal and human studies have also demonstrated a reduction in CBF following dexmedetomidine [7,8]. Karlsson et al demonstrated a reduction of CBF in dogs anesthetized with 0.9% halothane; however, the authors could not determine if dexmedetomidine directly constricted the cerebral vasculature or blunted the cerebral vasodilatation induced by halothane [9]. Prielipp et al demonstrated decreases in CBF in 9 healthy adult volunteers using PET scanning [10].…”
Section: Discussionmentioning
confidence: 95%
“…Given its possible beneficial effects on ICP and cerebral blood flow (CBF), dexmedetomidine continues to gain popularity as an agent for sedation in patients with traumatic brain injury [5][6][7][8][9]. The effects of dexmedetomidine on ICP and CPP were evaluated by Talke et al in adult patients following transphenoidal pituitary resection [5].…”
Section: Discussionmentioning
confidence: 98%
“…Dexmedetomidine treatment of non-alcohol-related delirium has also been shown to shorten the number of delirium-and coma-free days, as compared with lorazepam therapy [19]. While there are no reports specifically addressing the use of dexmedetomidine in traumatic brain injury, there appears to be consensus in the literature that dexmedetomidine causes no change or only slight decreases in intracranial pressure [20][21][22][23]. Furthermore, experimental studies have demonstrated a role for dexmedetomidine as a neuroprotective agent [24,25].…”
Section: Discussionmentioning
confidence: 97%
“…Nakano recently reported that dexmedetomidine-induced cerebral hypoperfusion exacerbated ischemic brain injury in rats [28]. Hypotension was observed in 10 of 39 (26%) neurosurgical patients treated with dexmedetomidine infusions for sedation during intubation in the ICU [21]. Because of the FDA restriction on limiting the usage of dexmedetomidine very little has been reported about adverse effects from its long-term use.…”
Section: Discussionmentioning
confidence: 98%